Relationship between malocclusion severity and treatment stability in Class II nonextraction treatment - Caldas, Waleska Trovisco (2018)
Introduction: When planning Class II malocclusion treatment it is importat to consider the magnitude of the anteroposterior discrepancy, the treatment time, the amount of patient compliance needed and also the long-term stability of the results obtained. The aim of this study was to evaluate the Class II malocclusion nonextraction treatment stability, according to the initial anteroposterior discrepancy severity. Methods: Two groups of patients were selected according to the initial malocclusion severity. The Half-cusp Class II Group comprised 30 patients (16 boys, 14 girls) with an initial mean age of 13.15 years (S.D. 3.62) and the Complete Class II Group comprised 30 patients (15 boys, 15 girls) with an initial mean age of 11.99 years (S.D. 1.26). Lateral cephalograms, panoramic radiographs and dental casts were obtained at pretreatment (T1), posttreatment (T2), and at a minimum period of 2 years posttreatment (T3). Intragroup comparisons of changes in variables during the posttreatment period (T3T2) were made with paired t tests. The initial cephalometric characteristics and malocclusion severity, changes during the treatment period and during the posttreatment period were compared between groups using t tests. A multiple linear regression analysis was used to evaluate the influence of pretreatment characteristics and amount of treatment changes in the amount of posttreatment relapse. Results were regarded as significant at p<0.05. Results: During the posttreatment period (T2-T3) there were no significant differences between groups. The occlusal analysis demonstrated a small but significant relapse of molar relationship for both groups. The initial amount of overjet, the severity of canine and molar relationships and the amount of anteroposterior changes during treatment were significantly correlated to the amount of posttreatment molar relationship relapse. When subgroups of patients with matching treatment time were compared, there was significantly greater relapse in molar relationship in the Complete Class II Group. Conclusions: The initial Class II malocclusion anteroposterior discrepancy severity demonstrated a significant influence on the amount of posttreatment relapse. When treated without extractions, complete Class II malocclusion presented greater relapse than a less severe Class II molar relationship.